The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1986
DOI: 10.1111/j.1532-5415.1986.tb04301.x
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Antibiotic Use in Nursing Homes: A Quality Assessment

Abstract: In this evaluation of the prevalence and quality of systemic antibiotic use in nursing homes, 42 skilled nursing facilities (SNFs) and their 11 attached intermediate care facilities (ICFs) were surveyed. A random sample of 2238 patients (51%) from the total of 4378 beds was selected and of these, 7.7% of the total (8.6% of the SNF and 4.5% of the ICF) patients were on systemic antibiotics on the day of the survey. The most common suspected sites of infection were urinary tract (58.4%), lower respiratory tract … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
119
1

Year Published

1990
1990
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(127 citation statements)
references
References 16 publications
6
119
1
Order By: Relevance
“…It accounts for anywhere from 13% to 48% of all infections in nursing home residents [1,2] and is the second most common type of nosocomial infection in hospitalized patients, after urinary tract infections [3]. The overall mortality rate ranges from 20% to 50%, with a rate as high as 80% reported in some studies [4][5][6][7][8].…”
mentioning
confidence: 99%
“…It accounts for anywhere from 13% to 48% of all infections in nursing home residents [1,2] and is the second most common type of nosocomial infection in hospitalized patients, after urinary tract infections [3]. The overall mortality rate ranges from 20% to 50%, with a rate as high as 80% reported in some studies [4][5][6][7][8].…”
mentioning
confidence: 99%
“…Previous study have found relatively high rates of antimicrobial use and substantial inappropriate use of antimicrobial agents in nursing homes and longterm care facilities (Zimmer JG & Al, 1986;Crossley K & Al 1987;Jones SR & Al, 1987;Katz PR & Al, 1990;Yakabowich MR & Al, 1994;Pickering TD & Al, 1994;Montgomery P & Al, 1995). In addition to increasing the risk of colonization or infection with antimicrobial-resistant organisms, inappropriate antimicrobial use adds cost to resident care and may place the patient at increased risk for drug adverse reactions (Mylotte JM, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…A substantial proportion of antimicrobial treatment in nursing homes is considered inappropriate: from 30 to 75% of systemic antimicrobial agents (Zimmer JG & Al, 1986;Crossley K & Al 1987;Jones SR & Al, 1987;Katz PR & Al, 1990;Yakabowich MR & Al, 1994;Pickering TD & Al, 1994;Montgomery P & Al, 1995) and up to 60% of topical antimicrobial agents (Montgomery P & Al, 1995) are inappropriately used.…”
Section: Antimicrobial Agent Use In Nursing Homesmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, it is likely that noninstitutionalized community acquired pneumonia is frequently treated with amoxicillin. In addition, amoxicillin is not recommended as a therapy for pneumonia in nursing home patients and yet, in many nursing homes, the majority of pneumonias are currently treated with amoxicillin (1) . Is this inappropriate practice in the absence of clinical outcome data documenting impaired efficacy?…”
mentioning
confidence: 99%